Chlamydial genital infection in Addis Ababa, Ethiopia. A seroepidemiological survey. Issue 6 (December 1982) - Forsey, T; Darougar, S; Dines, R J; Wright, D J; Friedmann, P S
Abstract : A seroepidemiological survey was undertaken in Addis Ababa to assess the prevalence of chlamydial genital infections among patients attending a sexually transmitted diseases (STD) clinic and patients with no overt genital symptoms. In the STD clinic patients antibodies to Chlamydia trachomatis serotypes D to K (genital types) were detected in 68 of 210 (32.4%) men and in 72 of 159 (45.3%) women, a rate of exposure as high or higher than that found in Europe. Serological evidence of active chlamydial infection was present in 26.7% of men and 28.9% of women. Women were at risk of contracting STD, including chlamydial infections, at the age of 14 years or earlier. The titres of antichlamydial IgG were extremely high in some patients attending the STD clinic, with titres of between 1/512 and 1/8192 in 9.5% of men and 13.2% of women. This suggests that some patients had severe or disseminated chlamydial disease. The prevalence of exposure to chlamydial genital infections among 148 patients with no overt genital disease was 14.2%, which is significantly higher than that found in the United Kingdom. Among the total of 517 patients tested the prevalence of exposure to trachoma, lymphogranuloma venereum, and Chlamydia psittaci agents was very low.